Financial regulation in Japan: a sixth year review of the Financial Services Agency - Hoshi, Takeo; Ito, Takatoshi (Journal of Financial Stability, 2004)
The paper provides a critical review of the Financial Services Agency (FSA) of Japan since its establishment in June 1998 (as the Financial Supervisory Agency) to June 2004. During the six year period, the FSA faced the challenge of addressing severe insolvency problems in banking as well as life insurance industries. The paper argues that the initial separation of the supervisory role (in the Financial Supervisory Agency and the Financial Reconstruction Commission) and the policy planning role (in the Ministry of Finance) was useful in the sense it allowed the FSA to have a firm stance on the insolvency problem that was partially created by the failure of the past financial regulatory policy. Even after the creation of the FSA, the Bank of Japan remained as another bank supervisor. This seems have made the central bank reluctant in relaxing monetary policy out of the fear that such loose monetary policy would actually discourage re-organization of banking industry. This suggests a problem of having the central bank as a bank supervisor. For the life insurance companies, the FSA (both old and new) has not been successful in intervening (using prompt corrective action) before the failures. Finally, the paper also points out the important role of the leadership at the FSA that shapes the financial regulation, and suggests a problem of appointing a politician to this role.